Loss of m6A Methyltransferase METTL5 Promotes Cardiac Hypertrophy Through Epitranscriptomic Control of SUZ12 Expression - Han, Yanchuang; Du, Tailai; Guo, Siyao; Wang, Lu; Dai, Gang; Long, Tianxin; Xu, Ting; Zhuang, Xiaodong; Liu, Chen; Li, Shujuan; Zhang, Dihua; Liao, Xinxue; et al. (Frontiers in Cardiovascular Medicine, 2022)
Enhancement of protein synthesis from mRNA translation is one of the key steps supporting cardiomyocyte hypertrophy during cardiac remodeling. The methyltransferase-like5 (METTL5), which catalyzes m6A modification of 18S rRNA at position A1832, has been shown to regulate the efficiency of mRNA translation during the differentiation of ES cells and the growth of cancer cells. It remains unknown whether and how METTL5 regulates cardiac hypertrophy. In this study, we have generated a mouse model, METTL5-cKO, with cardiac-specific depletion of METTL5 in vivo. Loss function of METTL5 promotes pressure overload-induced cardiomyocyte hypertrophy and adverse remodeling. The regulatory function of METTL5 in hypertrophic growth of cardiomyocytes was further confirmed with both gain- and loss-of-function approaches in primary cardiomyocytes. Mechanically, METTL5 can modulate the mRNA translation of SUZ12, a core component of PRC2 complex, and further regulate the transcriptomic shift during cardiac hypertrophy. Altogether, our study may uncover an important translational regulator of cardiac hypertrophy through m6A modification.